Analysis of Islamic Youth Organization Leadership Style Mosque - Prayogi, Ichsan Adil; Rajeba, Halizsa Nadia (Jurnal Komunikasi Profesional, 2023)
This research discusses how a leadership style in a mosque Islamic youth organization can create a conducive situation and be able to manage any conflicts that occur. This research uses Rensis Likert’s theory of leadership style, namely, absolute rulers, semi-absolute rulers, advisors & invitees as well. This research uses descriptive qualitative research methods, where this approach aims to provide a comprehensive and in-depth view of the subject under study, namely leadership style & conflict management in an Islamic youth mosque in Serang City. By taking the locus of a mosque Islamic youth organization, the author tries to analyze how the leadership style is applied by the mosque’s Islamic youth organization. The results of the research in this article indicate that the leadership style carried out by the chairman of Risma Masjid At-Taqwa is a participatory leadership style that always involves its members to make decisions so that joint decisions are created. In addition, the chairman of Risma also sometimes provides motivation, advice, or guidance to its members to be more enthusiastic about carrying out their duties. The communication that is carried out is also two-way communication, where there is reciprocity between members and the leader, the communication is also open and interactive.